2022
DOI: 10.3389/fphar.2022.963054
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in the Molecular Mechanisms, Therapeutic Targets, and Drug Development of Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal interstitial lung disease. Recent studies have identified the key role of crosstalk between dysregulated epithelial cells, mesenchymal, immune, and endothelial cells in IPF. In addition, genetic mutations and environmental factors (e.g., smoking) have also been associated with the development of IPF. With the recent development of sequencing technology, epigenetics, as an intermediate link between gene expression and environmental impacts, has also been reported t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 273 publications
(263 reference statements)
1
25
0
Order By: Relevance
“…IPF is the most common form of chronic interstitial pneumonia. Although its etiology is unknown, imbalance of apoptosis of alveolar epithelial cells or fibroblasts is one of the important pathogenic mechanisms ( Ma et al, 2022b ). TGF-β enhanced the expression of DOCK2 and the FMT marker α-SMA in primary human lung fibroblast (HLF), and DOCK2 knockdown also dramatically attenuated the TGF-β-induced expression of the FMT marker.…”
Section: Role Of Dock2 In Diseasesmentioning
confidence: 99%
“…IPF is the most common form of chronic interstitial pneumonia. Although its etiology is unknown, imbalance of apoptosis of alveolar epithelial cells or fibroblasts is one of the important pathogenic mechanisms ( Ma et al, 2022b ). TGF-β enhanced the expression of DOCK2 and the FMT marker α-SMA in primary human lung fibroblast (HLF), and DOCK2 knockdown also dramatically attenuated the TGF-β-induced expression of the FMT marker.…”
Section: Role Of Dock2 In Diseasesmentioning
confidence: 99%
“…Evaluation of chest computed tomography (CT) supports the early diagnosis of ILDs [ 4 , 5 ]. Recent studies have identified the key role of crosstalk among dysregulated epithelial cells, mesenchymal cells, immune cells, endothelial cells, genetic mutations and environmental factors (e.g., smoking) in idiopathic pulmonary fibrosis, a subtype of IIP [ 6 ]. Patients with IIPs occasionally have clinical features suggesting the presence of autoimmune diseases, including positive autoantibodies, without meeting the diagnostic criteria for any CTD.…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF), which primarily affects older male smokers, is the paradigm of chronic progressive idiopathic fibrosis. It is characterized with a histopathological and radiological point of view by the usual interstitial pneumonia (UIP) pattern [ 1 , 2 ]. IPF’s natural course is unpredictable and the pathophysiological mechanisms underlying the disease, the anatomical remodeling and progression, are currently under investigation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…More relevant, accurate biomarkers to prognosticate and guide management for patients affected by this disease are still needed. Current paradigms into IPF pathogenesis, a disease as lethal as malignant disorders, hypothesize altered apoptosis mechanisms as well as changes in cellular and intracellular pathways [ 1 , 2 ]. Epithelial damage, fibroblasts activation and proliferation, cell senescence, and aberrant immunological responses were all considered as relevant in this complex scenario [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%